Composite ZIF-8 with Cs3Bi2I9 to Enhance the Photodegradation Ability on Methylene Blue - Tao Tang; Haoran Zhang; Hexu Wang; Xiaoyu Dou; Jianfeng Wen; Li Jiang (Molecules)
The development of green, efficient, and reusable photocatalysts is important for pollution degradation. In recent years, Cs3Bi2I9 has been shown to be an effective photocatalyst. However, the rapid recombination of electrons and holes weakens the photocatalytic activity. In this work, the photogenerated electron transfer rate was promoted by ZIF-8 compositing with Cs3Bi2I9, which effectively improved the pollutant degradation. After 50 min of visible light irradiation, Cs3Bi2I9/ZIF-8 removed up to 98.2% of methylene blue (MB), which was 4.15 times higher than that of Cs3Bi2I9 alone. In addition, the Cs3Bi2I9/ZIF-8 composite still exhibited high photocatalytic activity after three cycling experiments. Our research offers a simple and efficient method for enhancing the photocatalytic activity of lead-free halide perovskites.